Solving economic dispatch problem using MATLAB optimization toolbox / Anis Nurhidayati Othman - Othman, Anis Nurhidayati (2009)
In economic dispatch problem, the objective is minimizes the total generation cost and fulfills the equality and inequality constraints. This thesis attempts to use Matlab Optimization Toolbox to solve economic dispatch problem. The objective of this study is to minimize the fuel cost while considering losses. The proposed method was tested on two system consisting three generator units and six generator units. The results show that the Matlab Optimization Toolbox can be used to solve the economic dispatch problem.